Violence against lesbian adolescents in the school environment and its consequences: integrative review (Research, Society and Development, 2021)
Objective: discuss the scientific evidence produced about the impact of violence in the school environment on the mental health of lesbian adolescents. Methods: integrative literature review, using controlled descriptors and alternative terms in the following databases: MEDLINE via PubMed, WOS, LILACS, SCOPUS, CINAHL, SciELO and BDENF. Results: four articles were selected that strongly relate the experiences of violence and victimization against lesbians with problems related to mental health and risk indicators. Females showed higher numbers than males regarding substance use, risk behaviors and mental disorders. Conclusion: it’s positive to say that the degrees of experiences of violence and insecurity in the school environment of lesbian youngs are different from those of heterosexual youngs. The role of nurses in the context of adolescents’ sexual health should aim to identify situations of vulnerability and, before them, promote the free exercise of the perception of sexuality, body autonomy, recognition of sexual rights, health, prevention and control of suffering psycho-emotional wear.